Comparison of piezosurgery and conventional rotatory technique in transalveolar extraction of mandibular third molars: A pilot study - Nouman Rashid; Vivekanandhan Subbiah; Padmanidhi Agarwal; Shailesh Kumar; Adity Bansal; Neeraj; Srinivas Gosla Reddy; Ashi Chug (Elsevier, 2020)
Objectives: To compare the postoperative outcomes in impacted mandibular third molar extraction using piezosurgery and conventional rotary technique; and to assess the stress levels in both the techniques by measuring salivary cortisol levels. Methods: Ten patients with symmetrical impacted lower third molars were included in this split mouth pilot study. Measurements for mouth opening and swelling were taken preoperatively on the day of surgery and 1 week after surgery. Pain was evaluated using Visual Analog Scale (VAS) from first postoperative day for six consecutive days. Saliva collection for analysis of cortisol levels was done at four time intervals - before starting the procedure, immediately after the procedure, 20 min and 1 week later. The mean in two groups was compared using paired t-test/Wilcoxon signed rank test as applicable. Friedman test was used to compare multiple readings of pain and salivary cortisol. Results: Reduction in mouth opening was more in rotary group than piezosurgery group but was not statistically significant (p = 0.092). Increase in facial swelling was more in the rotary group than piezosurgery group with statistically significant values (p = 0.020). Rotary group had higher values for postoperative pain as compared to piezosurgery on all the days and the difference was statistically significant on each day except second postoperative day. Salivary cortisol levels were elevated in both the groups with the mean values higher in group I (rotary) than in group II (Piezosurgery). Conclusion: Extraction of impacted lower third molar results in more favourable outcome when carried out by piezosurgery technique. Further studies are needed to compare the salivary cortisol response in rotary and piezosurgery techniques.